The Web-Based Academic Field Trip Bibliography: A Multi-Use Library Tool: Theme: All Topics - Joseph, Lura E. (Issues in Science and Technology Librarianship, 2004)
Field trip courses are part of the academic curriculum of many disciplines, especially in the sciences. This article examines the process of creating web-based field trip bibliographies in support of field trip courses, and their value to academic librarians as tools for reference service, instruction, collection development, partnering with teaching faculty, and public relations.